2013
DOI: 10.1016/j.msec.2012.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of titanium soaked in 5M NaOH or 5M KOH solutions

Abstract: Commercially pure titanium plates/coupons and pure titanium powders were soaked for 24 h in 5 M NaOH and 5 M KOH solutions, under identical conditions, over the temperature range of 37° to 90°C. Wettability of the surfaces of alkali-treated cpTi coupons were studied by using contact angle goniometry. cpTi coupons soaked in 5 M NaOH or 5 M KOH solutions were found to have hydrophilic surfaces. Hydrous alkali titanate nanofibers and nanotubes were identified with SEM/EDXS and grazing incidence XRD. Surface areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 70 publications
6
44
1
Order By: Relevance
“…Analysis within as-Ti group found that KOH etching increased the wettability of the surface with contact angle value of 25.27±0.95° lower than NaOH etching of 38.64±1.03°. Similar results also reported by Kim et al [16]. Potassium ion has a better reactivity compared to sodium ion.…”
Section: Figure 2 the Contact Angles Measurement Of Alkali And Alkalsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis within as-Ti group found that KOH etching increased the wettability of the surface with contact angle value of 25.27±0.95° lower than NaOH etching of 38.64±1.03°. Similar results also reported by Kim et al [16]. Potassium ion has a better reactivity compared to sodium ion.…”
Section: Figure 2 the Contact Angles Measurement Of Alkali And Alkalsupporting
confidence: 91%
“…Initial soaking of as-Ti and ab-Ti in NaOH gave the Ra value ~0.3-0.5µm greater than Ra in KOH treatment. Alkali treatment leads to the development of submicron-or nano roughness on Ti surface [16] Theoretically, potassium was slightly reactive than sodium. This might cause the outer layer of oxide Ti surface to completely dissolved and activated to form a more homogeneous oxide film.…”
Section: Results and Discussion Surface Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 (a), (b), and (c) show the pore morphology that formed on the surface of the Ti disk, and many researchers have reported that such a morphology can only be obtained when Ti is immersed into an NaOH solution [12,13]. The increase in temperature during heat treatment densifies the pores and changes them into rod-like features.…”
Section: Resultsmentioning
confidence: 99%
“…The FG sample with a contact angle of 20°, is more hydrophilic than the others. Contact angle on a surface is defined by the Young equation and the shape of a drop resting on a surface depends on the material properties of the drop, the atmosphere surrounding it, and most importantly the surface [62]. The superhydrophilic behavior in FG and H20T samples could be attributed to the finer microstructure and less porous structure which promotes capillary effect [63].…”
Section: Accepted Manuscriptmentioning
confidence: 99%